Cytogenetic and testicular histological alterations induced by sulphur dioxide in dried apricot leather - Zaki, Eiman I.; EL-Mahdy, Ahmed R.; EL-Gamal, Hanan M.; El-Seedy, Ayman S. (Cellular and Molecular Biology, 2021)
Sulphur dioxide (SO2) is used as a preservative in food to prevent its discolouration, and to inhibit the growth of bacteria. Little data is available concerning its in vivo hazardous impact.The present study is therefore designed to examine the cyto-genotoxic potential and the testicular histological alterations in adult mice, induced by SO2 present in the dried apricot leather used to prepare the oriental drink Qamar Al-Deen. Two different forms of drinks were tested; cold and boiled drinks. Animals were placed into 4 groups. The first group received distilled water as a negative control.The second and third groups received orally the drink for 28 days in the form of a cold and a boiled drink, respectively. Animals of the fourth group received cyclophosphamide, they were used as a positive control for cyto-genotoxic tests. The chromosomal aberrations, as well as sperm abnormalities, were significantly elevated in animals that received the two different drink preparations. The mitotic index significantly decreased in comparison with negative and positive controls. Furthermore, histological examination showed different degrees of alterations in the testis. Our results suggest that the presence of SO2 inside the apricot leather might be responsible for these changes. Thus, these remarkable hazardous effects of SO2 on male albino mice could be used as a potential guide for the prediction of its human health impact. Furthermore, consumers could be advised to prevent excessive consumption of the drink (Qamar Al-Deen) prepared from dried apricot leather.